2007
DOI: 10.1007/s00167-007-0391-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arthroscopic meniscectomy on the long-term prognosis for the discoid lateral meniscus

Abstract: This study compared the long-term clinical and radiological outcomes, according to the extent of arthroscopic meniscectomy, of complete and incomplete types of the discoid lateral meniscus. A total of 125 discoid menisci (74 complete and 51 incomplete types) without significant cartilage erosion at the time of surgery were included. The extent of meniscectomy was decided along with tear patterns and the stability of the discoid meniscus. Both clinical and radiological results were evaluated after total or part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…However, this study lacked any statistical analysis as a result of its small sample size (50 patients) and did not address survivorship. Although long-term followup studies exist for knee arthroscopy for meniscectomies and meniscal repairs [8,9,17,25], the conclusions from the knee cannot be extrapolated to the hip. Furthermore, results from short-and long-term studies of both hip and knee arthroscopy have resulted in conflicting conclusions [17].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, this study lacked any statistical analysis as a result of its small sample size (50 patients) and did not address survivorship. Although long-term followup studies exist for knee arthroscopy for meniscectomies and meniscal repairs [8,9,17,25], the conclusions from the knee cannot be extrapolated to the hip. Furthermore, results from short-and long-term studies of both hip and knee arthroscopy have resulted in conflicting conclusions [17].…”
Section: Introductionmentioning
confidence: 96%
“…Although long-term followup studies exist for knee arthroscopy for meniscectomies and meniscal repairs [8,9,17,25], the conclusions from the knee cannot be extrapolated to the hip. Furthermore, results from short-and long-term studies of both hip and knee arthroscopy have resulted in conflicting conclusions [17]. In one study, at an average followup of 5 years after hip arthroscopy, chondromalacia and osteoarthritis did not predict eventual THA or poor post-operative mHHS [15], whereas another study at 2 years followup, and the previously discussed study at 10 years followup [4], showed a clear influence of preoperative arthritis on postoperative surveys or the mHHS [4,10].…”
Section: Introductionmentioning
confidence: 96%
“…The finding of a discoid meniscus is often incidental, but may become symptomatic if torn, most commonly in the posterior segment [1]. The shape, thickness, poor vascularization, and often flimsy capsular attachment cause discoid menisci to be prone to injury leading to pain, swelling, giving way, locking, and clunking [1,[5][6][7]. Discoid meniscal tears most commonly occur during childhood or adolescence, but some patients may reach middle age without an issue [1,8].…”
Section: Introductionmentioning
confidence: 96%
“…partial meniscectomy and saucerization) or transplant a whole meniscus in the form of a size-matched allograft [5,9]. Optimal management for this condition is controversial given the upfront cost differential between the two treatment options: the more expensive meniscal allograft transplantation compared with standard partial meniscectomy.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, several authors investigated the outcomes of arthroscopic saucerization and reported promising results with few complications [3,4,6,[8][9][10][11][12][13][14][15][16][17][18][19]. However, prognostic factors affecting the final outcomes are not well studied in relevant literature.…”
Section: Introductionmentioning
confidence: 98%